"Let me heare … if thou canst say": The Utility of the Prayer Book Catechism (1549–1604). (January 2022) - Keane, Drew N.
This article explores the catechism in the Book of Common Prayer, shedding light on the emergence of instructional writing from oral instruction. The 1549 text evinces qualities of preliterate oral communication identified by Ong. By contrast, the 1604 addendum reveals a trend toward modern plain style, which is even more pronounced in the 1647 Westminster Shorter Catechism. The evidence indicates the oral features were useful to the text's technical aims. What Ramist plain style gains in precision and objectivity comes at the cost of other useful features, such as reiteration, contextualization, and agonism, which (in Tannen's phrase) involve a greater relative focus on interpersonal involvement between speaker and auditor/ reader.